Glass articles
The glass item with a controlled Li2O-Al2O3-SiO2 composition maintains the color of the colored layer on cooker top plates, addressing color impairment issues and ensuring transparency and thermal stability.
Patent Information
- Application Number
- JP2020154671
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-09-15
- Publication Date
- 2025-01-29
- Estimated Expiration
- 2040-09-15
Smart Images

Figure 0007623628000031 
Figure 0007623628000032 
Figure 0007623628000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a glass article suitable for a cooking top plate. [Background technology]
[0002] Li2O-Al2O3-SiO2-based crystallized glass substrates having a low thermal expansion coefficient are used for top plates of cookers such as electromagnetic cookers, radiant heater cookers, and gas cookers (see, for example, Patent Documents 1 to 3). The glass substrates of such cooker top plates have a cooking surface and a back surface located on the inside of the cooker.
[0003] A colored layer is generally formed on the rear surface of the glass substrate in a top plate for a cooking appliance for the purposes of improving the design and concealing the internal structure of the cooking appliance. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Special Publication No. 39-21049 [Patent Document 2] Special Publication No. 40-20182 [Patent Document 3] Japanese Patent Application Publication No. 1-308845 Summary of the Invention [Problem to be solved by the invention]
[0005] However, Li2O-Al2O3-SiO2 crystallized glass is colored due to TiO2, Fe2O3, etc., which impairs the color of the colored layer and ultimately impairs the appearance of the cooker top plate.
[0006] An object of the present invention is to provide a glass article suitable for a top plate for a cooker without impairing the color tone of a colored layer. [Means for solving the problem]
[0007] The glass article of the present invention is characterized by comprising a Li2O-Al2O3-SiO2-based crystallized glass plate having a lightness L* of 70 or more, a chromaticity a* within ±5, and a chromaticity b* within ±5 at a thickness of 3 mm, and a colored layer formed on the back surface of the Li2O-Al2O3-SiO2-based crystallized glass plate.
[0008] In the glass article of the present invention, the Li2O-Al2O3-SiO2-based crystallized glass plate preferably contains, by mass%, 40 to 90% SiO2, 5 to 30% Al2O3, 1 to 10% Li2O, less than 0 to 2% TiO2, 0 to 20% SnO2, 1 to 20% ZrO2, 0 to 10% MgO, 50 to 10% P2O, and less than 0 to 2% Sb2O3+As2O3.
[0009] In the glass article of the present invention, the Li2O-Al2O3-SiO2 crystallized glass plate preferably has a colorless and transparent appearance.
[0010] In the glass article of the present invention, the Li2O-Al2O3-SiO2 crystallized glass plate preferably has a thickness of 3 mm and a transmittance at a wavelength of 300 nm of 10% or more.
[0011] The glass article of the present invention has a thermal expansion coefficient of 30×10 -7 / °C or less.
[0012] The glass article of the present invention has a thermal expansion coefficient of 30×10 -7 / °C or less.
[0013] The top plate for a cooker of the present invention is characterized by comprising the above-mentioned glass article. Effect of the Invention
[0014] According to the present invention, it is possible to provide a glass article suitable for a top plate for a cooking appliance without impairing the color tone of the colored layer. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1 is a schematic front cross-sectional view showing a glass article according to one embodiment of the present invention. [Diagram 2] This is the measurement result of reflected chromaticity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Preferred embodiments will be described below. However, the following embodiments are merely examples, and the present invention is not limited to the following embodiments.
[0017] (Glass item 1) FIG. 1 is a schematic front cross-sectional view showing a glass article 1 according to one embodiment of the present invention. As shown in FIG. 1, the glass article 1 includes a Li2O-Al2O3-SiO2-based crystallized glass plate 2 and a colored layer 3 formed on the back surface of the Li2O-Al2O3-SiO2-based crystallized glass plate 2. The Li2O-Al2O3-SiO2-based crystallized glass plate 2 has a cooking surface 2a, which is a main surface on one side, and a back surface 2b, which is a main surface on the other side. The cooking surface 2a is the surface on which a cooking utensil such as a pot or a frying pan is placed. The back surface 2b is the surface facing the heating device on the inside side of the cooking appliance. Therefore, the cooking surface 2a and the back surface 2b are in a front-back relationship.
[0018] (Li2O-Al2O3-SiO2 crystallized glass plate 2) The Li2O-Al2O3-SiO2 crystallized glass plate 2 preferably contains, by mass%, 40-90% SiO2, 5-30% Al2O3, 1-10% Li2O, 0-2% or less TiO2, 0-20% SnO2, 1-20% ZrO2, 0-10% MgO, 50-10% P2O, and 0-2% or less Sb2O3+As2O3. In the following description of the content of each component, "%" means "% by mass" unless otherwise specified.
[0019] SiO2 is a component that forms the skeleton of glass and also constitutes Li2O-Al2O3-SiO2 crystals. The content of SiO2 is preferably 40-90%, 52-80%, 55-75%, 56-70%, 59-70%, 60-70%, 60-69.5%, 60.5-69.5%, 61-69.5%, 61.5-69.5%, 62-69.5%, 62.5-69.5%, 63-69.5%, and particularly 63.5-69.5%. If the content of SiO2 is too low, the thermal expansion coefficient tends to be high, making it difficult to obtain crystallized glass with excellent thermal shock resistance. In addition, chemical durability tends to decrease. On the other hand, if the content of SiO2 is too high, the meltability of glass decreases, the viscosity of the glass melt increases, making it difficult to clarify or mold the glass, and productivity tends to decrease. In addition, the time required for crystallization becomes longer, which tends to reduce productivity.
[0020] Al2O3 is a component that forms the skeleton of glass and also constitutes Li2O-Al2O3-SiO2 crystals. In addition, Al2O3 is a component that coordinates around the crystal nucleus and forms a core-shell structure. The presence of the core-shell structure makes it difficult for crystal nucleus components to be supplied from outside the shell, so that the crystal nucleus is less likely to enlarge and a large number of small crystal nuclei are more likely to be formed. The content of Al2O3 is preferably 5 to 30%, 8 to 30%, 9 to 28%, 10 to 27%, 12 to 27%, 14 to 27%, 16 to 27%, 17 to 27%, 18 to 27%, 18 to 26.5%, 18.1 to 26.5%, 19 to 26.5%, 19.5 to 26.5%, 20 to 26.5%, 20.5 to 26.5%, and particularly 20.8 to 25.8%. If the content of Al2O3 is too low, the thermal expansion coefficient tends to be high, making it difficult to obtain crystallized glass with excellent thermal shock resistance. Also, chemical durability tends to decrease. Furthermore, the crystal nuclei become large, making the crystallized glass more likely to become cloudy, and the color of the colored layer 3 is more likely to be damaged. On the other hand, if the content of Al2O3 is too high, the meltability of the glass decreases, the viscosity of the glass melt increases, making it difficult to clarify the glass, making it difficult to mold the glass, and making it easy to decrease productivity. Also, mullite crystals tend to precipitate, causing the glass to devitrify, making the crystallized glass more likely to break.
[0021] Li2O is a component that constitutes Li2O-Al2O3-SiO2 crystals, and has a large effect on crystallinity, and also reduces the viscosity of glass, improving the meltability and formability of glass. The content of Li2O is preferably 1-10%, 2-10%, 2-8%, 2.5-6%, 2.8-5.5%, 2.8-5%, 3-5%, 3-4.5%, 3-4.2%, and particularly 3.2-4%. If the content of Li2O is too low, mullite crystals tend to precipitate and the glass tends to devitrify. In addition, when crystallizing glass, Li2O-Al2O3-SiO2 crystals are difficult to precipitate, making it difficult to obtain crystallized glass with excellent thermal shock resistance. Furthermore, the meltability of glass decreases, the viscosity of the glass melt increases, making it difficult to clarify the glass, and making it difficult to mold the glass, which tends to reduce productivity. On the other hand, if the Li2O content is too high, the crystallinity becomes too strong, the glass tends to become easily devitrified, and the crystallized glass becomes easily broken.
[0022] SiO2, Al2O3, and Li2O are the main components of the β-quartz solid solution, which is the main crystal, and Li2O and Al2O3 compensate for each other's charges to form a solid solution in the SiO2 skeleton. By containing these three components in an appropriate ratio, crystallization proceeds efficiently, making it possible to manufacture at low cost. The mass ratio of (SiO2+Al2O3) / Li2O is preferably 20 or more, 20.2 or more, 20.4 or more, 20.6 or more, 20.8 or more, and especially 21 or more.
[0023] TiO2 is a nucleation component for precipitating crystals in the crystallization process. On the other hand, if it is contained in a large amount, it significantly intensifies the coloring of the glass and easily impairs the color of the colored layer 3. In particular, zirconia titanate crystals containing ZrO2 and TiO2 act as crystal nuclei, but electrons transition from the valence band of the ligand oxygen to the conduction band of the central metal zirconia and titanium (LMCT transition), which contributes to the coloring of the crystallized glass. In addition, if titanium remains in the remaining glass phase, an LMCT transition can occur from the valence band of the SiO2 skeleton to the conduction band of the tetravalent titanium in the remaining glass phase. In addition, a dd transition occurs in the trivalent titanium in the remaining glass phase, which contributes to the coloring of the crystallized glass. Furthermore, when titanium and iron coexist, an ilmenite (FeTiO3)-like coloring is expressed. It is also known that when titanium and tin coexist, the yellow color is intensified. For this reason, the content of TiO2 is preferably 0 to less than 2%, 0 to 1%, 0 to less than 0.5%, 0 to 0.48%, 0 to 0.46%, 0 to 0.44%, 0 to 0.42%, 0 to 0.4%, 0 to 0.38%, 0 to 0.36%, 0 to 0.34%, 0 to 0.32%, 0 to 0.3%, 0 to 0.28%, 0 to 0.26%, 0 to 0.24%, 0 to 0.22%, 0 to 0.2%, 0 to 0.18%, 0 to 0.16%, 0 to 0.14%, 0 to 0.12%, and particularly 0 to 0.1%. However, since TiO2 is easily mixed in as an impurity, if TiO2 is to be completely removed, the raw material batch becomes expensive and the manufacturing cost tends to increase. In order to suppress an increase in manufacturing costs, the lower limit of the TiO2 content is preferably 0.0003% or more, 0.0005% or more, 0.001% or more, 0.005% or more, 0.01% or more, particularly preferably 0.02% or more.
[0024] SnO2 acts as a clarifier. It is also a necessary component for efficient crystal precipitation during the crystallization process. On the other hand, if it is contained in a large amount, it significantly intensifies the coloring of glass. The SnO2 content is 0-20%, over 0-20%, 0.05-20%, 0.1-10%, 0.1-5%, 0.1-4%, 0.1-3%, 0.15-3%, 0.2-3%, 0.2-2.7%, 0.2-2.4%, 0.25-2.4%, 0.3-2.4%, 0.35-2.4%, 0.4-2.4%, 0.45-2.4%, 0.5-2.4%, 0. It is preferable that the content of SnO2 is 5 to 2.35%, 0.5 to 2.3%, 0.5 to 2.2%, 0.5 to 2.1%, 0.5 to 2.05%, 0.5 to 2%, 0.5 to 1.95%, 0.5 to 1.93%, 0.5 to 1.91%, 0.5 to 1.9%, 0.5 to 1.88%, 0.5 to 1.85%, 0.5 to 1.83%, 0.5 to 1.81%, and particularly 0.5 to 1.8%. If the content of SnO2 is too small, it becomes difficult to clarify the glass, and the productivity is likely to decrease. In addition, crystal nuclei are not sufficiently formed, and coarse crystals are precipitated, which may cause the glass to become cloudy or break. On the other hand, if the content of SnO2 is too large, the coloring of the crystallized glass may become strong, and the color of the colored layer 3 may be easily damaged. In addition, the amount of SnO2 evaporated during melting increases, which tends to increase the environmental impact.
[0025] ZrO2 is a nucleation component for precipitating crystals during the crystallization process. The ZrO2 content is 1-20%, 1-15%, 1-10%, 1-5%, 1.5-5%, 1.75-4.5%, 1.75-4.4%, 1.75-4.3%, 1.75-4.2%, 1.75-4.1%, 1.75-4%, 1.8-4%, 1.85-4%, 1.9-4%, 1.95-4%, 2-4%, 2.05-4%, It is preferable that the content of ZrO2 is 2.1 to 4%, 2.15 to 4%, 2.2 to 4%, 2.25 to 4%, 2.3 to 4%, 2.3 to 3.95%, 2.3 to 3.9%, 2.3 to 3.95%, 2.3 to 3.9%, 2.3 to 3.85%, 2.3 to 3.8%, more than 2.7 to 3.8%, 2.8 to 3.8%, 2.9 to 3.8%, and particularly 3 to 3.8%. If the content of ZrO2 is too small, crystal nuclei are not sufficiently formed, and coarse crystals are precipitated, the crystallized glass becomes cloudy, and the color of the colored layer 3 may be easily impaired or broken. On the other hand, if the content of ZrO2 is too large, coarse ZrO2 crystals are precipitated, the glass becomes easily devitrified, and the crystallized glass becomes easily broken.
[0026] TiO2 and ZrO2 are components that can function as crystal nuclei. Ti and Zr are homologous elements, and have similar electronegativity and ionic radius. For this reason, they tend to have similar molecular conformations as oxides, and it has been found that in the coexistence of TiO2 and ZrO2, phase separation is likely to occur in the early stages of crystallization. For this reason, within the range in which coloring is permitted, the mass ratio of TiO2 / ZrO2 is preferably 0.0001 to 5.0, 0.0001 to 4.0, 0.0001 to 3.0, 0.0001 to 2.5, 0.0001 to 2.0, 0.0001 to 1.5, 0.0001 to 1.0, 0.0001 to 0.5, 0.0001 to 0.4, and particularly 0.0001 to 0.3. If TiO2 / ZrO2 is too small, the raw material batch becomes expensive and the manufacturing cost tends to increase. On the other hand, if TiO2 / ZrO2 is too large, the crystal nucleation rate will be slow, which may increase the production cost.
[0027] SnO2+ZrO2 is preferably 1-30%, 1.1-30%, 1.1-27%, 1.1-24%, 1.1-21%, 1.1-20%, 1.1-17%, 1.1-14%, 1.1-11%, 1.1-9%, 1.1-7.5%, 1.4-7.5%, 1.8-7.5%, 2.0-7.5%, 2.2-7%, 2.2-6.4%, 2.2-6.2%, 2.2-6%, 2.3-6%, 2.4-6%, 2.5-6%, and particularly preferably 2.8-6%. If SnO2+ZrO2 is too small, crystal nuclei are less likely to precipitate and crystallization is less likely to occur. On the other hand, if the content of SnO2+ZrO2 is too high, the crystal nuclei become large, the crystallized glass becomes easily clouded, and the color tone of the colored layer 3 is easily impaired.
[0028] SnO2 has the effect of promoting phase separation of glass. In order to efficiently cause phase separation while keeping the liquidus temperature low (while reducing the risk of devitrification due to initial phase precipitation) and to rapidly perform nucleation and crystal growth in the subsequent steps, the mass ratio of SnO2 / (SnO2+ZrO2) is preferably 0.01 to 0.99, 0.01 to 0.98, 0.01 to 0.94, 0.01 to 0.90, 0.01 to 0.86, 0.01 to 0.82, 0.01 to 0.78, 0.01 to 0.74, 0.01 to 0.70, 0.03 to 0.70, and particularly preferably 0.05 to 0.70.
[0029] In addition, SnO2 reacts with SnO2 → SnO + 1 / 2O2 at high temperatures, releasing O2 gas into the molten glass. This reaction is known as the fining mechanism of SnO2, and the O2 gas released during the reaction enlarges the tiny bubbles present in the molten glass and releases them outside the glass system, and also has a "stirring effect" of mixing the molten glass. In the Li2O-Al2O3-SiO2-based crystallized glass of the present invention, the content of SiO2 and Al2O3 accounts for the majority, and since these components are difficult to dissolve, it is necessary to contain these three components in a suitable ratio in order to efficiently form a homogeneous molten glass. The mass ratio of (SiO2 + Al2O3) / SnO2 is 44 or more, 44.3 or more, 44.7 or more, 45 or more, or 45.2 or more. It is preferable that it is 45.4 or more, 45.6 or more, 45.8 or more, and especially 46 or more.
[0030] Al2O3 / (SnO2+ZrO2) is preferably 7.1 or less, 7.05 or less, 7.0 or less, 6.95 or less, 66.9 or less, 6.85 or less, 6.8 or less, 6.75 or less, 6.7 or less, 6.65 or less, 6.6 or less, 6.55 or less, 6.5 or less, 6.45 or less, 6.4 or less, 6.35 or less, 6.3 or less, 6.25 or less, 6.2 or less, 6.15 or less, 6.1 or less, 6.05 or less, 6.0 or less, 5.98 or less, 5.95 or less, 5.92 or less, 5.9 or less, 5.8 or less, 5.7 or less, 5.6 or less, and particularly 5.5 or less. If Al2O3 / (SnO2+ZrO2) is too large, nucleation does not proceed efficiently, making it difficult to crystallize efficiently. On the other hand, if Al2O3 / (SnO2+ZrO2) is too small, the crystal nuclei become large, the crystallized glass becomes easily clouded, and the color of the colored layer 3 is easily impaired. For this reason, the lower limit of Al2O3 / (SnO2+ZrO2) is preferably 0.01 or more.
[0031] MgO is a component that dissolves in Li2O-Al2O3-SiO2 crystals and increases the thermal expansion coefficient of the Li2O-Al2O3-SiO2 crystals. The content of MgO is preferably 0-10%, 0-8%, 0-6%, 0-5%, 0-4.5%, 0-4%, 0-3.5%, 0.02-3.5%, 0.05-3.5%, 0.08-3.5%, 0.1-3.5%, 0.1-3.3%, 0.1-3%, 0.13-3%, 0.15-3%, 0.17-3%, 0.19-3%, 0.2-2.9%, 0.2-2.7%, 0.2-2.5%, 0.2-2.3%, 0.2-2.2%, 0.2-2.1%, and particularly preferably 0.2-2%. If the content of MgO is too low, the thermal expansion coefficient tends to be too low. Also, volumetric shrinkage occurs during crystal precipitation, but the amount of volumetric shrinkage may be too large. Also, the difference in thermal expansion coefficient between the crystal phase after crystallization and the remaining glass phase becomes large, so the crystallized glass may be easily broken. If the content of MgO is too high, the crystallinity becomes too strong, making it prone to devitrification and the crystallized glass to be easily broken. Also, the thermal expansion coefficient tends to be too high.
[0032] P2O5 is a component that suppresses the precipitation of coarse ZrO2 crystals. The content of P2O5 is preferably 0 to 10%, 0 to 8%, 0 to 6%, 0 to 5%, 0 to 4%, 0 to 3.5%, 0.02 to 3.5%, 0.05 to 3.5%, 0.08 to 3.5%, 0.1 to 3.5%, 0.1 to 3.3%, 0.1 to 3%, 0.13 to 3%, 0.15 to 3%, 0.17 to 3%, 0.19 to 3%, 0.2 to 2.9%, 0.2 to 2.7%, 0.2 to 2.5%, 0.2 to 2.3%, 0.2 to 2.2%, 0.2 to 2.1%, 0.2 to 2%, and particularly preferably 0.3 to 1.8%. If the P2O5 content is too low, coarse ZrO2 crystals will precipitate, causing the glass to devitrify and the crystallized glass to break easily.On the other hand, if the P2O5 content is too high, the amount of Li2O-Al2O3-SiO2 crystals precipitated will decrease, and the thermal expansion coefficient will tend to increase.
[0033] As2O3 and Sb2O3 are highly toxic and may pollute the environment during the glass manufacturing process or waste glass treatment. For this reason, it is preferable that Sb2O3+As2O3 is less than 2%, 1% or less, 0.7% or less, 0.7%, 0.65% or less, 0.6% or less, 0.55% or less, 0.5% or less, 0.45% or less, 0.4% or less, 0.35% or less, 0.3% or less, 0.25% or less, 0.2% or less, 0.15% or less, 0.1% or less, and in particular, substantially none (specifically, less than 0.1 mass%). When As2O3 or Sb2O3 is contained, these components may function as a clarifier or nucleation agent.
[0034] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention may contain the following components in addition to the above components in the glass composition.
[0035] Na2O is a component that can be dissolved in Li2O-Al2O3-SiO2 crystals, and has a large effect on crystallinity, and also reduces the viscosity of glass to improve the melting and moldability of glass. It is also a component for adjusting the thermal expansion coefficient and refractive index of crystallized glass. The content of Na2O is preferably 0-10%, 0-8%, 0-6%, 0-5%, 0-4.5%, 0-4%, 0-3.5%, 0-3%, 0-2.7%, 0-2.4%, 0-2.1%, 0-1.8%, and particularly 0-1.5%. If the content of Na2O is too high, the crystallinity becomes too strong, the glass becomes easily devitrified, and the crystallized glass becomes easily broken. In addition, the ionic radius of Na cations is larger than that of Li cations and Mg cations, which are the main crystal constituents, and is therefore difficult to be incorporated into the crystals, so that Na cations after crystallization tend to remain in the remaining glass (glass matrix). Therefore, if the Na2O content is too high, a refractive index difference between the crystal phase and the remaining glass is likely to occur, the crystallized glass is likely to become cloudy, and the color of the colored layer 3 is likely to be impaired. However, since Na2O is likely to be mixed in as an impurity, if Na2O is to be completely removed, the raw material batch becomes expensive and the manufacturing cost tends to increase. In order to suppress the increase in manufacturing cost, the lower limit of the Na2O content is preferably 0.0003% or more, 0.0005% or more, and particularly 0.001% or more.
[0036] K2O is a component that can be dissolved in Li2O-Al2O3-SiO2 crystals, and has a large effect on crystallinity, and also reduces the viscosity of glass to improve the melting and moldability of glass. It is also a component for adjusting the thermal expansion coefficient and refractive index of crystallized glass. The content of K2O is 0-10%, 0-8%, 0-6%, 0-5%, 0-4.5%, 0-4%, 0-3.5%, 0-3%, 0-2.7%, 0-2.4%, 0-2.1%, 0-1.8%, 0-1.5%, 0-1.4%, 0-1.3%, 0-1.2%. It is preferably 0-1.1%, 0-1%, 0-0.9%, and particularly preferably 0.1-0.8%. If the content of K2O is too high, the crystallinity becomes too strong, the glass becomes easily devitrified, and the crystallized glass becomes easily broken. In addition, the ionic radius of K cations is larger than that of Li cations and Mg cations, which are the main crystal constituents, and is difficult to be incorporated into the crystal, so that K cations after crystallization tend to remain in the remaining glass. For this reason, if the content of K2O is too high, the refractive index difference between the crystal phase and the remaining glass is likely to occur, the crystallized glass is likely to become cloudy, and the color of the colored layer 3 is likely to be impaired. However, since K2O is likely to be mixed in as an impurity, if K2O is to be completely removed, the raw material batch tends to become expensive and the manufacturing cost tends to increase. In order to suppress the increase in manufacturing cost, the lower limit of the content of K2O is preferably 0.0003% or more, 0.0005% or more, and particularly 0.001% or more.
[0037] Li2O, Na2O, and K2O are components that improve the melting and moldability of glass, but if the content of these components is too high, the low-temperature viscosity will drop too much, and the glass may flow too much during crystallization. Li2O, Na2O, and K2O are also components that can deteriorate the weather resistance, water resistance, chemical resistance, etc. of glass before crystallization. If the glass before crystallization is deteriorated by moisture, etc., the desired crystallization behavior and therefore the desired properties may not be obtained. On the other hand, ZrO2 is a component that functions as a nucleating agent, and has the effect of crystallizing preferentially at the beginning of crystallization and suppressing the flow of the remaining glass. In addition, ZrO2 efficiently fills the voids in the glass network, which is mainly composed of SiO2 skeleton, and has the effect of inhibiting the diffusion of protons and various chemical components in the glass network, improving the weather resistance, water resistance, chemical resistance, etc. of glass before crystallization. In order to obtain crystallized glass with the desired shape and properties, (Li2O+Na2O+K2O) / ZrO2 should be appropriately controlled. The mass ratio of (Li2O+Na2O+K2O) / ZrO2 is preferably 2.0 or less, 1.98 or less, 1.96 or less, 1.94 or less, 1.92 or less, and particularly preferably 1.90 or less.
[0038] CaO is a component that reduces the viscosity of glass and improves the melting and moldability of glass. It is also a component for adjusting the thermal expansion coefficient and refractive index of crystallized glass. The content of CaO is preferably 0-10%, 0-8%, 0-6%, 0-5%, 0-4.5%, 0-4%, 0-3.5%, 0-3%, 0-2.7%, 0-2.4%, 0-2.1%, 0-1.8%, and particularly 0-1.5%. If the content of CaO is too high, the glass is easily devitrified and the crystallized glass is easily broken. In addition, the ionic radius of Ca cations is larger than that of Li cations and Mg cations, which are the main crystal constituents, and is difficult to be incorporated into the crystal, so that Ca cations after crystallization are likely to remain in the remaining glass. For this reason, if the content of CaO is too high, a refractive index difference between the crystal phase and the remaining glass is easily generated, the crystallized glass is easily clouded, and the color of the colored layer 3 is easily impaired. However, since CaO is easily mixed in as an impurity, if one tries to completely remove CaO, the raw material batch becomes expensive and the manufacturing cost tends to increase. In order to suppress the increase in manufacturing cost, the lower limit of the CaO content is preferably 0.0001% or more, 0.0003% or more, and particularly 0.0005% or more.
[0039] SrO is a component that reduces the viscosity of glass and improves the melting and moldability of glass. It is also a component for adjusting the thermal expansion coefficient and refractive index of crystallized glass. The content of SrO is preferably 0-10%, 0-8%, 0-6%, 0-5%, 0-4.5%, 0-4%, 0-3.5%, 0-3%, 0-2.7%, 0-2.4%, 0-2.1%, 0-1.8%, 0-1.5%, and particularly 0-1%. If the content of SrO is too high, the glass is easily devitrified and the crystallized glass is easily broken. In addition, the ionic radius of Sr cation is larger than that of Li cation and Mg cation, which are the main crystal constituents, and is difficult to be incorporated into the crystal, so that Sr cation after crystallization is likely to remain in the remaining glass. For this reason, if the SrO content is too high, a difference in refractive index between the crystal phase and the remaining glass is likely to occur, the crystallized glass is likely to become cloudy, and the color of the colored layer 3 is likely to be impaired. However, since SrO is likely to be mixed in as an impurity, if SrO is to be completely removed, the raw material batch becomes expensive and the manufacturing cost tends to increase. In order to suppress the increase in manufacturing cost, the lower limit of the SrO content is preferably 0.0001% or more, 0.0003% or more, and particularly 0.0005% or more.
[0040] BaO is a component that reduces the viscosity of glass and improves the melting and moldability of glass. It is also a component for adjusting the thermal expansion coefficient and refractive index of crystallized glass. The content of BaO is preferably 0-10%, 0-8%, 0-6%, 0-5%, 0-4.5%, 0-4%, 0-3.5%, 0-3%, 0-2.7%, 0-2.4%, 0-2.1%, 0-1.8%, 0-1.5%, and particularly 0-1%. If the content of BaO is too high, crystals containing Ba are precipitated, the glass is easily devitrified, and the crystallized glass is easily broken. In addition, the ionic radius of Ba cation is larger than that of Li cation and Mg cation, which are the main crystal constituents, and is difficult to be incorporated into the crystal, so that Ba cation after crystallization is likely to remain in the remaining glass. Therefore, if the BaO content is too high, a difference in refractive index between the crystal phase and the remaining glass is likely to occur, the crystallized glass is likely to become cloudy, and the color of the colored layer 3 is likely to be impaired. However, since BaO is likely to be mixed in as an impurity, if BaO is to be completely removed, the raw material batch becomes expensive and the manufacturing cost tends to increase. In order to suppress the increase in manufacturing cost, the lower limit of the BaO content is preferably 0.0001% or more, 0.0003% or more, and particularly 0.0005% or more.
[0041] MgO, CaO, SrO, and BaO are components that improve the meltability and moldability of glass, but if the content of these components is too high, the low-temperature viscosity will drop too much, and the glass may flow too much during crystallization. On the other hand, ZrO2 is a component that functions as a nucleating agent, and has the effect of crystallizing preferentially at the beginning of crystallization and suppressing the flow of the remaining glass. In order to obtain crystallized glass with the desired shape and characteristics, (MgO+CaO+SrO+BaO) / ZrO2 should be appropriately controlled. (MgO+CaO+SrO+BaO) / ZrO2 is preferably 0 to 3, 0 to 2.8, 0 to 2.6, 0 to 2.4, 0 to 2.2, 0 to 2.1, 0 to 2, 0 to 1.8, 0 to 1.7, 0 to 1.6, and particularly 0 to 1.5, in terms of mass ratio.
[0042] Na2O, K2O, CaO, SrO, and BaO are likely to remain in the remaining glass after crystallization. Therefore, if the total amount of these is too large, the refractive index difference between the crystal phase and the remaining glass is likely to occur, and the crystallized glass is likely to become cloudy. Therefore, Na2O+K2O+CaO+SrO+BaO is preferably 8% or less, 7% or less, 6% or less, 5% or less, 4.5% or less, 4% or less, 3.5% or less, 3% or less, 2.7% or less, 2.42% or less, 2.415% or less, 2.410% or less, 2.405% or less, and particularly 2.4% or less.
[0043] Li2O, Na2O, K2O, MgO, CaO, SrO, and BaO are components that improve the meltability and formability of glass. In addition, glass melts containing a large amount of MgO, CaO, SrO, and BaO tend to have a gradual change in viscosity (viscosity curve) relative to temperature, while glass melts containing a large amount of Li2O, Na2O, and K2O tend to have a rapid change. If the change in the viscosity curve is too gradual, the glass will continue to flow even after being molded into a desired shape, making it difficult to obtain the desired shape. On the other hand, if the change in the viscosity curve is too rapid, the glass melt will solidify during molding, making it difficult to obtain the desired shape. For this reason, (MgO+CaO+SrO+BaO) / (Li2O+Na2O+K2O) should be appropriately controlled. The mass ratio of (MgO+CaO+SrO+BaO) / (Li2O+Na2O+K2O) is preferably 0 to 2, 0 to 1.8, 0 to 1.5, 0 to 1.2, 0 to 1, 0 to 0.9, 0 to 0.8, 0 to 0.7, 0 to 0.6, 0 to 0.5, and particularly preferably 0 to 0.45.
[0044] ZnO is a component that dissolves in Li2O-Al2O3-SiO2 crystals and has a large effect on crystallinity. It is also a component for adjusting the thermal expansion coefficient and refractive index of the crystallized glass. The content of ZnO is preferably 0-10%, 0-8%, 0-6%, 0-5%, 0-4.5%, 0-4%, 0-3.5%, 0-3%, 0-2.7%, 0-2.4%, 0-2.1%, 0-1.8%, 0-1.5%, and particularly preferably 0-1%. If the content of ZnO is too high, the crystallinity becomes too strong, which makes the glass prone to devitrification and breakage. However, since ZnO is easily mixed in as an impurity, if ZnO is to be completely removed, the raw material batch becomes expensive and the manufacturing cost tends to increase. In order to suppress the increase in manufacturing cost, the lower limit of the content of ZnO is preferably 0.0001% or more, 0.0003% or more, and particularly preferably 0.0005% or more.
[0045] In Li2O-Al2O3-SiO2 crystallized glass, Li cations, Mg cations, and Zn cations are components that are easily dissolved in β-quartz solid solutions, and compared with Ba cations, they are considered to be components that contribute less to the increase in the refractive index of the remaining glass after crystallization. In addition, Li2O, MgO, and ZnO function as fluxes when vitrifying raw materials, so they can be said to be important components in manufacturing colorless and transparent crystallized glass at low temperatures. Li2O is an essential component for achieving low expansion, and must be contained at 1% or more. In order to achieve the desired thermal expansion coefficient, etc., the necessary amount of Li2O must be contained, but if the contents of MgO and ZnO are also increased accordingly, the viscosity of the glass may decrease too much. If the low-temperature viscosity decreases too much, the softening fluidity of the glass during firing may become too large, making it difficult to crystallize into the desired shape. In addition, if the high-temperature viscosity decreases too much, the thermal load on the manufacturing equipment decreases, but the convection speed during heating increases, and there is a risk that refractories and other materials may be easily physically eroded. Therefore, it is preferable to control the content ratio of Li2O, MgO, and ZnO, and in particular, it is preferable to control the total amount of MgO and ZnO relative to Li2O, which has a high function as a flux. Therefore, it is preferable to make the mass ratio of (MgO+ZnO) / Li2O small, such as 0.394 or less, 0.393 or less, 0.392 or less, 0.391 or less, and especially 0.390 or less, or to make it large, such as 0.755 or more, 0.756 or more, 0.757 or more, 0.758 or more, and especially 0.759 or more.
[0046] B2O3 is a component that reduces the viscosity of glass and improves the meltability and moldability of glass. It is also a component that may be involved in the ease of phase separation during crystal nucleation. The content of B2O3 is preferably 0-10%, 0-8%, 0-6%, 0-5%, 0-4.5%, 0-4%, 0-3.5%, 0-3%, 0-2.7%, 0-2.4%, 0-2.1%, 0-1.8%, and particularly 0-1.5%. If the content of B2O3 is too high, the amount of B2O3 evaporated during melting increases, which increases the environmental load. However, since B2O3 is easily mixed in as an impurity, if B2O3 is to be completely removed, the raw material batch becomes expensive and the manufacturing cost tends to increase. In order to suppress the increase in manufacturing cost, B2O3 may be contained in an amount of 0.0001% or more, 0.0003% or more, and particularly 0.0005% or more.
[0047] It is known that in Li2O-Al2O3-SiO2 crystallized glass, a phase separation region is formed in the glass before the formation of crystal nuclei, and then crystal nuclei composed of TiO2, ZrO2, etc. are formed in the phase separation region. Since SnO2, ZrO2, P2O5, TiO2, and B2O3 are strongly involved in the phase separation formation, the ratios of SnO2+ZrO2+P2O5+TiO2+B2O3 are 1.5-30%, 1.5-26%, 1.5-22%, 1.5-20%, 1.5-18%, 1.5-16%, 1.5-15%, 1.8-15%, 2.1-15%, 2.4-15%, 2.5-15%, 2.8-15%, 2.8-13%, 2.8-12%, 2.8-11%, and 2.8-10%. , 3 to 9.5%, 3 to 9.2%, and particularly 3 to 9%, and SnO2 / (SnO2+ZrO2+P2O5+TiO2+B2O3) is preferably 0.06 or more, 0.07 or more, 0.08 or more, 0.09 or more, 0.1 or more, 0.103 or more, 0.106 or more, 0.11 or more, 0.112 or more, 0.115 or more, 0.118 or more, 0.121 or more, 0.124 or more, 0.127 or more, 0.128 or more, and particularly preferably 0.13 or more. If SnO2+ZrO2+P2O5+TiO2+B2O3 is too little, it becomes difficult to form a phase separation region and crystallize. On the other hand, if SnO2+ZrO2+P2O5+TiO2+B2O3 is too much and / or SnO2 / (SnO2+ZrO2+P2O5+TiO2+B2O3) is too small, the phase separation region becomes large, the crystallized glass becomes easily clouded, and the color of the colored layer 3 is easily impaired. The upper limit of SnO2 / (SnO2+ZrO2+P2O5+TiO2+B2O3) is not particularly limited, but is practically 0.9 or less.
[0048] Fe2O3 is a component that enhances the coloring of glass, especially a component that significantly enhances coloring by interacting with TiO2 and SnO2. The content of Fe2O3 is preferably 0.10% or less, 0.08% or less, 0.06% or less, 0.05% or less, 0.04% or less, 0.035% or less, 0.03% or less, 0.02% or less, 0.015% or less, 0.013% or less, 0.012% or less, 0.011% or less, 0.01% or less, 0.009% or less, 0.008% or less, 0.007% or less, 0.006% or less, 0.005% or less, 0.004% or less, 0.003% or less, and especially 0.002% or less. However, since Fe2O3 is easily mixed in as an impurity, if Fe2O3 is to be completely removed, the raw material batch becomes expensive and the manufacturing cost tends to increase. In order to suppress an increase in production costs, the lower limit of the Fe2O3 content is preferably 0.0001% or more, 0.0002% or more, 0.0003% or more, 0.0005% or more, and particularly preferably 0.001% or more.
[0049] When titanium and iron coexist, ilmenite (FeTiO3)-like coloring may appear. In particular, in Li2O-Al2O3-SiO2 crystallized glass, titanium and iron components that do not precipitate as crystal nuclei or main crystals after crystallization remain in the remaining glass, and the appearance of the above coloring may be promoted. In terms of composition design, it is possible to reduce the amount of these components, but since TiO2 and Fe2O3 are easily mixed in as impurities, if they are to be completely removed, the raw material batch becomes expensive and the manufacturing cost tends to increase. Therefore, in order to suppress the manufacturing cost, TiO2 and Fe2O3 may be contained within the above-mentioned range, and in order to make the manufacturing cost cheaper, both components may be contained within the range in which coloring is allowed. In such a case, the mass ratio of TiO2 / (TiO2+Fe2O3) is preferably 0.001 to 0.999, 0.003 to 0.997, 0.005 to 0.995, 0.007 to 0.993, 0.009 to 0.991, 0.01 to 0.99, 0.1 to 0.9, 0.15 to 0.85, 0.2 to 0.8, 0.25 to 0.25, 0.3 to 0.7, 0.35 to 0.65, and particularly preferably 0.4 to 0.6. This makes it easier to obtain colorless and highly transparent crystallized glass at low cost.
[0050] Pt is a component that can be mixed into glass in the form of ions, colloids, metals, etc., and it causes yellow to brown coloring, which tends to impair the color of the colored layer 3. This tendency becomes more pronounced after crystallization. Furthermore, after careful investigation, it was found that the inclusion of Pt affects the nucleation and crystallization behavior of the crystallized glass, which may lead to the glass becoming cloudy. For this reason, it is preferable that the Pt content is 7 ppm or less, 6 ppm or less, 5 ppm or less, 4 ppm or less, 3 ppm or less, 2 ppm or less, 1.6 ppm or less, 1.4 ppm or less, 1.2 ppm or less, 1 ppm or less, 0.9 ppm or less, 0.8 ppm or less, 0.7 ppm or less, 0.6 ppm or less, 0.5 ppm or less, 0.45 ppm or less, 0.40 ppm or less, 0.35 ppm or less, and particularly 0.30 ppm or less. Although the inclusion of Pt should be avoided as much as possible, when using general melting equipment, it may be necessary to use Pt components to obtain homogeneous glass. For this reason, if Pt is to be completely removed, the manufacturing cost tends to increase. In the case where coloring is not adversely affected, in order to suppress an increase in manufacturing costs, the lower limit of the Pt content is preferably 0.0001 ppm or more, 0.001 ppm or more, 0.005 ppm or more, 0.01 ppm or more, 0.02 ppm or more, 0.03 ppm or more, 0.04 ppm or more, 0.05 ppm or more, 0.06 ppm or more, and particularly 0.07 ppm or more. In addition, in the case where coloring is permitted, Pt may be used as a nucleation agent that promotes the precipitation of main crystals, similar to ZrO2 and TiO2. In that case, Pt may be used as a nucleation agent alone, or may be used as a nucleation agent in combination with other components. In addition, when Pt is used as a nucleation agent, the form is not particularly important (colloid, metal crystal, etc.).
[0051] Rh is a component that can be mixed into glass in the form of ions, colloids, metals, etc., and, like Pt, tends to cause yellow to brown coloring and make the crystallized glass opaque, which easily impairs the color of the colored layer 3. For this reason, the content of Rh is preferably 7 ppm or less, 6 ppm or less, 5 ppm or less, 4 ppm or less, 3 ppm or less, 2 ppm or less, 1.6 ppm or less, 1.4 ppm or less, 1.2 ppm or less, 1 ppm or less, 0.9 ppm or less, 0.8 ppm or less, 0.7 ppm or less, 0.6 ppm or less, 0.5 ppm or less, 0.45 ppm or less, 0.40 ppm or less, 0.35 ppm or less, and particularly 0.30 ppm or less. Although the mixing of Rh should be avoided as much as possible, when using general melting equipment, it may be necessary to use Rh members to obtain homogeneous glass. For this reason, if Rh is to be completely removed, the manufacturing cost tends to increase. In the case where coloring is not adversely affected, in order to suppress an increase in manufacturing costs, the lower limit of the Rh content is preferably 0.0001 ppm or more, 0.001 ppm or more, 0.005 ppm or more, 0.01 ppm or more, 0.02 ppm or more, 0.03 ppm or more, 0.04 ppm or more, 0.05 ppm or more, 0.06 ppm or more, and particularly 0.07 ppm or more. In addition, in the case where coloring is permitted, Rh may be used as a nucleating agent similar to ZrO2 or TiO2. In that case, Rh may be used as a nucleating agent alone or in combination with other components. In addition, when Rh is used as a nucleating agent to promote the precipitation of main crystals, the form is not particularly important (colloid, metal crystal, etc.).
[0052] In addition, Pt+Rh is 9ppm or less, 8ppm or less, 7ppm or less, 6ppm or less, 5ppm or less, 4.75ppm or less, 4.5ppm or less, 4.25ppm or less, 4ppm or less, 3.75ppm or less, 3.5ppm or less, 3.25ppm or less, 3ppm or less, 2.75ppm or less, 2.5ppm or less, 2.25ppm or less, 2ppm or less, 1.75ppm or less, 1.5ppm It is preferable that the concentration is 1.25 ppm or less, 1 ppm or less, 0.95 ppm or less, 0.9 ppm or less, 0.85 ppm or less, 0.8 ppm or less, 0.75 ppm or less, 0.7 ppm or less, 0.65 ppm or less, 0.60 ppm or less, 0.55 ppm or less, 0.50 ppm or less, 0.45 ppm or less, 0.40 ppm or less, 0.35 ppm or less, and particularly 0.30 ppm or less. Although the inclusion of Pt and Rh should be avoided as much as possible, when using general melting equipment, it may be necessary to use Pt and Rh components to obtain homogeneous glass. Therefore, if Pt and Rh are to be completely removed, the manufacturing cost tends to increase. In the case where there is no adverse effect on coloration, in order to suppress an increase in production costs, the lower limit of Pt+Rh is preferably 0.0001 ppm or more, 0.001 ppm or more, 0.005 ppm or more, 0.01 ppm or more, 0.02 ppm or more, 0.03 ppm or more, 0.04 ppm or more, 0.05 ppm or more, 0.06 ppm or more, and particularly preferably 0.07 ppm or more.
[0053] In developing glass materials, it is common to use various crucibles to produce glasses of various compositions. For this reason, platinum and rhodium that have evaporated from the crucible are often present inside the electric furnace used for melting. It has been confirmed that Pt and Rh present inside the electric furnace are mixed into the glass. In order to control the amount of Pt and Rh mixed in, it is possible to control the Pt and Rh content in the glass by selecting the raw materials and crucible materials used, attaching a quartz lid to the crucible, lowering the melting temperature, shortening the melting time, etc.
[0054] In addition to the above components, trace components such as H2, CO2, CO, H2O, He, Ne, Ar, and N2 may be contained up to 0.1% each, as long as they do not adversely affect coloring. In addition, if Ag, Au, Pd, Ir, V, Cr, Sc, Ce, Pr, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Ac, Th, Pa, U, etc. are intentionally added to glass, the raw material cost tends to increase and the manufacturing cost tends to increase. On the other hand, when glass containing Ag, Au, etc. is irradiated with light or heat treated, aggregates of these components are formed, and crystallization can be promoted from these aggregates. In addition, Pd, etc. have various catalytic effects, and by containing them, it is possible to impart unique functions to glass or crystallized glass. In consideration of these circumstances, when the purpose is to promote crystallization or to impart other functions, the above components may be contained in an amount of 1% or less, 0.5% or less, 0.3% or less, or 0.1% or less, respectively, and if not, the amount is preferably 500 ppm or less, 300 ppm or less, 100 ppm or less, and particularly preferably 10 ppm or less.
[0055] Furthermore, as long as there is no adverse effect on coloring, SO3, MnO, Cl2, Y2O3, MoO3, La2O3, WO3, HfO2, Ta2O5, Nd2O3, Nb2O5, RfO2, etc. may be contained in a total amount of up to 10%. However, since the raw material batches of the above components are expensive and tend to increase manufacturing costs, they may not be added unless there are special circumstances. In particular, since HfO2 has a high raw material cost and Ta2O5 may be a conflict mineral, the total amount of these components is preferably 5% or less by mass, 4% or less, 3% or less, 2% or less, 1% or less, 0.5% or less, 0.4% or less, 0.3% or less, 0.2% or less, 0.1% or less, 0.05% or less, less than 0.05%, 0.049% or less, 0.048% or less, 0.047% or less, 0.046% or less, and especially 0.045% or less.
[0056] The Li2O-Al2O3-SiO2-based crystallized glass plate 2 has a β-OH value of 0.001 to 2 / mm, and is preferably 0.01 to 1.5 / mm, 0.02 to 1.5 / mm, 0.03 to 1.2 / mm, 0.04 to 1.5 / mm, 0.05 to 1 / mm, 0.06 to 1 / mm, 0.07 to 1 / mm, 0.08 to 0.9 / mm, 0.08 to 0.85 / mm, It is preferable that the β-OH value is 0.08 to 0.8 / mm, 0.08 to 0.75 / mm, 0.08 to 0.7 / mm, 0.08 to 0.65 / mm, 0.08 to 0.6 / mm, 0.08 to 0.55 / mm, 0.08 to 0.54 / mm, 0.08 to 0.53 / mm, 0.08 to 0.52 / mm, 0.08 to 0.51 / mm, and particularly 0.08 to 0.5 / mm. If the β-OH value is too small, the crystal nucleus formation rate in the crystallization process is slowed down, and the amount of crystal nuclei generated is likely to be small. As a result, the number of coarse crystals increases, the crystallized glass becomes cloudy, the transparency is easily impaired, and the color of the colored layer 3 is easily impaired. The reason why crystallization progresses due to a large β-OH value is not completely clear, but it is expected that one of the reasons is that the β-OH group weakens the bond of the glass skeleton and reduces the viscosity of the glass. Another factor is thought to be the presence of β-OH groups in glass, which facilitates the movement of components that can function as crystal nuclei, such as Zr. On the other hand, if the β-OH value is too large, bubbles are likely to form at the interface between the glass and metal glass manufacturing furnace components containing Pt, etc., or glass manufacturing furnace components equipped with refractories, which can easily deteriorate the quality of the glass product. The β-OH value varies depending on the raw materials used, the melting atmosphere, the melting temperature, the melting time, etc., and these conditions can be changed as necessary to adjust the β-OH value. The "β-OH value" refers to the value calculated using the following formula after measuring the transmittance of glass using FT-IR.
[0057] β-OH value = (1 / X)log(T1 / T2) X: Glass thickness (mm) T1: Reference wavelength 3846cm -1 Transmittance (%) T2: Hydroxyl group absorption wavelength 3600cm -1 Minimum transmittance (%) near
[0058] That is, the preferred composition ranges of the Li2O-Al2O3-SiO2-based crystallized glass plate 2 are 50-75% SiO2, 10-30% Al2O3, 1-8% Li2O, 0-5% SnO2, 1-5% ZrO2, 0-10% MgO, 50-5% P2O, 0-less than 1.5% TiO2, (Li2O+Na2O+K2O) / ZrO2 0-1.5, TiO2 / (TiO2+Fe2O3) 0.01-0.99, (MgO+ZnO) / Li2O 0-0.8, and β-OH value 0.001-2 / mm. More preferably, the ranges are 50-75% SiO2, 10-30% Al2O3, 1-8% Li2O, more than 0-5% SnO2, 1-5% ZrO2, and 0-10% MgO. 0-10%, P2O50-5%, TiO20-less than 1.5%, (Li2O+Na2O+K2O) / ZrO20-1.5, TiO2 / (TiO2+Fe2O3)0.01-0.99, (MgO+ZnO) / Li2O0-0.8, (MgO+CaO+SrO+BaO) / (Li2O+Na2O+K2O)0-0.5, β-OH value is 0.001-2 / mm, and more preferably SiO250-75%, Al2O310-30%, Li2O1-8%, SnO20-5%, ZrO21-5%, MgO 0-10%, P2O50-5%, TiO20-less than 1.5%, (Li2O+Na2O+K2O) / ZrO20-1.5, TiO2 / (TiO2+Fe2O3)0.01-0.99, (MgO+ZnO) / Li2O 0-0.8, (MgO+CaO+SrO+BaO) / (Li2O+Na2O+K2O) 0-0.5, (MgO+CaO+SrO+BaO) / ZrO20-2, β-OH value is 0.001-2 / mm, and more preferably SiO250-75%, Al2O310-30%, Li2O 1-8%, SnO20-5%, ZrO21-5%, MgO 0~10%, P2O50~5%, TiO20~less than 1.5%, (Li2O+Na2O+K2O) / ZrO20~1.5, TiO2 / (TiO2+Fe2O3)0.01~0.99, (MgO+ZnO) / Li2O 0~0.8, (MgO+CaO+SrO+BaO) / (Li2O+Na2O+K2O) 0~0.5, (MgO+CaO+SrO+BaO) / ZrO20~2, SnO2 / (SnO2+ZrO2+P2O5+TiO2+B2O3) 0.06~0.9, β-OH value is 0.001-2 / mm, and more preferably, SiO2 50-75%, Al2O3 10-30%, Li2O 1-8%, SnO2 more than 0-5%, ZrO2 1-5%, MgO 0-10%, P2O 50-5%, TiO2 0-less than 1.5%, (Li2O+Na2O+K2O) / ZrO2 0-1.5, TiO2 / (TiO2+Fe2O3) 0.01-0.99, (MgO+ZnO) / Li2O 0-0.8, (MgO+CaO+SrO+BaO) / (Li2O+Na2O+K2O) 0-0.5, (MgO+CaO+SrO+BaO) / ZrO20-2, SnO2 / (SnO2+ZrO2+P2O5+TiO2+B2O3) 0.06-0.9, Pt+Rh 0-5ppm, β-OH value 0.001-2 / mm, and more preferably SiO2 50-75%, Al2O3 10-30%, Li2O 1-8%, SnO20-5%, ZrO2 1-5%, MgO 0-10%, P2O 50-5%, TiO20-less than 1.5%, (Li2O+Na2O+K2O) / ZrO20-1.5, TiO2 / (TiO2+Fe2O3) 0.01-0.99, (MgO+ZnO) / Li2O 0-0.394, (MgO+CaO+SrO+BaO) / (Li2O+Na2O+K2O) 0-0.5, (MgO+CaO+SrO+BaO) / ZrO20-2, SnO2 / (SnO2+ZrO2+P2O5+TiO2+B2O3) 0.06-0.9, Pt+Rh 0-5ppm, β-OH value 0.001-2 / mm. Particularly preferred are SiO2 50-75%, Al2O3 10-30%, Li2O 1-8%, SnO20-5%, ZrO2 1-5%, MgO 0~10%, P2O50~5%, TiO20~less than 1.5%, (Li2O+Na2O+K2O) / ZrO20~1.5, TiO2 / (TiO2+Fe2O3)0.01~0.99, (MgO+ZnO) / Li2O 0~0.394, (MgO+CaO+SrO+BaO) / (Li2O+Na2O+K2O) 0~0.5, (MgO+CaO+SrO+BaO) / ZrO20~2, SnO2 / (SnO2+ZrO2+P2O5+TiO2+B2O3) 0.06~0.9, Pt+Rh 0-5ppm, HfO2+Ta2O50-less than 0.05%, β-OH value is 0.001-2 / mm, Sb2O3+As2O3 less than 0.7%.
[0059] The Li2O-Al2O3-SiO2 crystallized glass plate 2 having the above composition tends to have a colorless and transparent appearance, and the color of the colored layer 3 is less likely to be impaired.
[0060] The Li2O-Al2O3-SiO2-based crystallized glass plate 2 has a lightness L* of 70% or more at a thickness of 3 mm, and is preferably 75 or more, 80 or more, 85 or more, 90 or more, 91 or more, 92 or more, 93 or more, 94 or more, 95 or more, 96 or more, 96.1 or more, 96.3 or more, and particularly 96.5 or more. If the lightness L* is too small, it tends to look grayish and dark regardless of the magnitude of chromaticity, and the color tone of the colored layer 3 is easily impaired.
[0061] The Li2O-Al2O3-SiO2 crystallized glass plate 2 has a chromaticity a* of ±5, ±4.5, ±4, ±3.6, ±3.2, ±2.8, ±2.4, ±2, ±1.8, ±1.6, ±1.4, ±1.2, ±1, ±0.9, ±0.8, ±0.7, ±0.6, and preferably ±0.5 at a thickness of 3 mm. If the brightness a* is too large in the negative direction, it tends to look green, and if it is too large in the positive direction, it tends to look red, which tends to impair the color of the colored layer 3.
[0062] The Li2O-Al2O3-SiO2 crystallized glass plate 2 has a chromaticity b* of ±5, ±4.5, ±4, ±3.6, ±3.2, ±2.8, ±2.4, ±2, ±1.8, ±1.6, ±1.4, ±1.2, ±1, ±0.9, ±0.8, ±0.7, ±0.6, and preferably ±0.5 at a thickness of 3 mm. If the brightness b* is too large in the negative direction, it tends to look blue, and if it is too large in the positive direction, it tends to look yellow, which tends to impair the color of the colored layer 3.
[0063] The Li2O-Al2O3-SiO2 crystallized glass plate 2 has a thickness of 3 mm and a transmittance at a wavelength of 200 nm of 0% or more, 2.5% or more, 5% or more, 10% or more, 12% or more, 14% or more, 16% or more, 18% or more, 20% or more, 22% or more, 24% or more, 26% or more, 28% or more, 30% or more, 32% or more, 34% or more, 36% or more, 38% or more, 40% or more, 40.5% or more, 41% or more, 41.5% or more, 42% or more, 42.5% or more, 43% or more, 43.5% or more, 44% or more, 44.5% or more, and particularly 45% or more. If the transmittance at a wavelength of 200 nm is too low, there is a risk that the desired transmittance cannot be obtained, and the color of the colored layer 3 is easily impaired.
[0064] The Li2O-Al2O3-SiO2 crystallized glass plate 2 has a thickness of 3 mm and a transmittance at a wavelength of 250 nm of 0% or more, 1% or more, 2% or more, 3% or more, 4% or more, 5% or more, 6% or more, 7% or more, 8% or more, 9% or more, 10% or more, 10.5% or more, 11% or more, 11.5% or more, 12% or more, 12.5% or more, 13% or more, 13.5% or more, 14% or more, 14.5% or more, 15% or more, 15.5% or more, and particularly preferably 16% or more. If the transmittance at a wavelength of 250 nm is too low, there is a risk that the desired transmittance cannot be obtained, and the color of the colored layer 3 is easily impaired.
[0065] The Li2O-Al2O3-SiO2 crystallized glass plate 2 has a thickness of 3 mm and a transmittance at a wavelength of 300 nm of 0% or more, 2.5% or more, 5% or more, 10% or more, 12% or more, 14% or more, 16% or more, 18% or more, 20% or more, 22% or more, 24% or more, 26% or more, 28% or more, 30% or more, 32% or more, 34% or more, 36% or more, 38% or more, 40% or more, 40.5% or more, 41% or more, 41.5% or more, 42% or more, 42.5% or more, 43% or more, 43.5% or more, 44% or more, 44.5% or more, and particularly 45% or more. If the transmittance at a wavelength of 300 nm is too low, there is a risk that the desired transmittance cannot be obtained, and the color of the colored layer 3 is easily impaired.
[0066] The Li2O-Al2O3-SiO2-based crystallized glass plate 2 has a thickness of 3 mm and a transmittance at a wavelength of 325 nm of preferably 0% or more, 2.5% or more, 5% or more, 10% or more, 12% or more, 14% or more, 16% or more, 18% or more, 20% or more, 22% or more, 24% or more, 26% or more, 28% or more, 30% or more, 32% or more, 34% or more, 36% or more, 38% or more, 40% or more, 42% or more, 44% or more, 46% or more, 48% or more, 50% or more, 52% or more, 54% or more, 56% or more, 57% or more, 58% or more, 59% or more, 60% or more, 61% or more, 62% or more, 63% or more, 64% or more, and particularly preferably 65% or more. If the transmittance at a wavelength of 325 nm is too low, there is a risk that the desired transmittance cannot be obtained, and the color tone of the colored layer 3 is easily impaired.
[0067] The Li2O-Al2O3-SiO2-based crystallized glass plate 2 has a thickness of 3 mm and a transmittance at a wavelength of 350 nm of 0% or more, 5% or more, 10% or more, 15% or more, 20% or more, 25% or more, 30% or more, 35% or more, 40% or more, 45% or more, 50% or more, 55% or more, 60% or more, 65% or more, 70% or more, 71% or more, 72% or more, 73% or more, 74% or more, 75% or more, 76% or more, 77% or more, 78% or more, 80% or more, 81% or more, 82% or more, or 83% or more. If the transmittance at a wavelength of 350 nm is too low, there is a risk that the desired transmittance cannot be obtained, and the color of the colored layer 3 is easily impaired.
[0068] The Li2O-Al2O3-SiO2-based crystallized glass plate 2 has a thickness of 3 mm and a transmittance at a wavelength of 380 nm of preferably 50% or more, 55% or more, 60% or more, 65% or more, 70% or more, 75% or more, 78% or more, 80% or more, 81% or more, 82% or more, 83% or more, and particularly preferably 84% or more. If the transmittance at a wavelength of 380 nm is too low, the yellow coloring becomes strong and the transparency of the crystallized glass decreases, which may make it impossible to obtain the desired transmittance, and the color of the colored layer 3 is easily impaired.
[0069] The Li2O-Al2O3-SiO2 crystallized glass plate 2 has a thickness of 3 mm and a transmittance at a wavelength of 800 nm of preferably 50% or more, 55% or more, 60% or more, 65% or more, 70% or more, 75% or more, 78% or more, 80% or more, 81% or more, 82% or more, 83% or more, 84% or more, 85% or more, 86% or more, 87% or more, and particularly preferably 88% or more. If the transmittance at a wavelength of 800 nm is too low, the color tends to turn green, which tends to impair the color of the colored layer 3.
[0070] The Li2O-Al2O3-SiO2 crystallized glass plate 2 has a thickness of 3 mm and a transmittance at a wavelength of 1200 nm of preferably 50% or more, 55% or more, 60% or more, 65% or more, 70% or more, 72% or more, 74% or more, 76% or more, 78% or more, 80% or more, 81% or more, 82% or more, 83% or more, 84% or more, 85% or more, 86% or more, 87% or more, 88% or more, and particularly preferably 89% or more. If the transmittance at a wavelength of 1200 nm is too low, the color tends to turn green, which tends to impair the color of the colored layer 3.
[0071] The Li2O-Al2O3-SiO2 crystallized glass plate 2 has a thickness of 3 mm and a transmittance change rate before and after crystallization at a wavelength of 300 nm of 50% or less, 48% or less, 46% or less, 44% or less, 42% or less, 40% or less, 38% or less, 37.5% or less, 37% or less, 36.5% or less, 36% or less, 35.5% or less, and particularly 35% or less. If the transmittance change rate before and after crystallization is small, it becomes possible to predict and control the transmittance after crystallization before crystallization, and it becomes easier to obtain the desired transmittance after crystallization. It is preferable that the transmittance change rate before and after crystallization is small not only at a wavelength of 300 nm but also in the entire wavelength range.
[0072] The Li2O-Al2O3-SiO2 crystallized glass plate 2 is in a glass state before crystallization and has a strain point (glass viscosity of about 10 14.5The temperature corresponding to dPa s is preferably 600°C or higher, 605°C or higher, 610°C or higher, 615°C or higher, 620°C or higher, 630°C or higher, 635°C or higher, 640°C or higher, 645°C or higher, 650°C or higher, and particularly preferably 655°C or higher. If the strain point is too low, the glass before crystallization is likely to break when molded.
[0073] The Li2O-Al2O3-SiO2 crystallized glass plate 2 is in a glass state before crystallization and is cooled to a temperature of about 10 13 The annealing point (temperature equivalent to dPa s) is preferably 680°C or higher, 685°C or higher, 690°C or higher, 695°C or higher, 700°C or higher, 705°C or higher, 710°C or higher, 715°C or higher, 720°C or higher, and particularly preferably 725°C or higher. If the annealing point is too low, the glass before crystallization is likely to break when molded.
[0074] The Li2O-Al2O3-SiO2 crystallized glass plate 2 is easily crystallized by heat treatment, so it has a softening point (glass viscosity is about 10) like common glasses such as soda-lime glass. 7.6 It is not easy to measure the temperature at which the thermal expansion curve of the glass before crystallization changes (the temperature corresponding to dPa·s). Therefore, in the Li2O-Al2O3-SiO2-based crystallized glass of the present invention, the temperature at which the slope of the thermal expansion curve of the glass before crystallization changes is taken as the glass transition temperature, and is treated as a substitute for the softening point. The Li2O-Al2O3-SiO2-based crystallized glass plate 2 preferably has a glass transition temperature of 680°C or higher, 685°C or higher, 690°C or higher, 695°C or higher, 700°C or higher, 705°C or higher, 710°C or higher, 715°C or higher, 720°C or higher, and particularly 725°C or higher, in the glass state before crystallization. If the glass transition temperature is too low, the glass will flow too much during crystallization, making it difficult to form it into a desired shape.
[0075] The liquidus temperature of the Li2O-Al2O3-SiO2 crystallized glass plate 2 is preferably 1540°C or less, 1535°C or less, 1530°C or less, 1525°C or less, 1520°C or less, 1515°C or less, 1510°C or less, 1505°C or less, 1500°C or less, 1495°C or less, 1490°C or less, 1485°C or less, 1480°C or less, 1475°C or less, 1470°C or less, 1465°C or less, 1460°C or less, 1455°C or less, 1450°C or less, 1445°C or less, 1440°C or less, 1435°C or less, 1430°C or less, 1425°C or less, 1420°C or less, 1415°C or less, and particularly 1410°C or less. If the liquidus temperature is too high, devitrification is likely to occur during production. On the other hand, if the temperature is 1480°C or lower, it is easy to manufacture using the roll method, etc., if the temperature is 1450°C or lower, it is easy to manufacture using the casting method, etc., and if the temperature is 1410°C or lower, it is easy to manufacture using the fusion method, etc.
[0076] The liquidus viscosity (logarithm of viscosity corresponding to liquidus temperature) of the Li2O-Al2O3-SiO2 crystallized glass plate 2 is preferably 2.70 or more, 2.75 or more, 2.80 or more, 2.85 or more, 2.90 or more, 2.95 or more, 3.00 or more, 3.05 or more, 3.10 or more, 3.15 or more, 3.20 or more, 3.25 or more, 3.30 or more, 3.35 or more, 3.40 or more, 3.45 or more, 3.50 or more, 3.55 or more, 3.60 or more, 3.65 or more, and particularly 3.70 or more. If the liquidus viscosity is too low, devitrification is likely to occur during production. On the other hand, if it is 3.40 or more, it becomes easy to manufacture by the roll method, etc., if it is 3.50 or more, it becomes easy to manufacture by the casting method, etc., and if it is 3.70 or more, it becomes easy to manufacture by the fusion method, etc.
[0077] It is preferable that the Li2O-Al2O3-SiO2 crystallized glass plate 2 has β-quartz solid solution precipitated as the main crystal. If β-quartz solid solution is precipitated as the main crystal, the crystal grain size is likely to be small, so that the crystallized glass is likely to transmit visible light, transparency is likely to be increased, and the color of the colored layer 3 is unlikely to be impaired. In addition, it is easy to bring the thermal expansion coefficient of the glass close to zero, so that the glass is unlikely to crack when heat-treated and cooled. Note that, in the Li2O-Al2O3-SiO2 crystallized glass plate 2, β-spodumene solid solution is precipitated by heat-treating the glass at a temperature higher than the crystallization conditions for precipitating β-quartz solid solution. The crystal grain size of β-spodumene solid solution tends to be larger than that of β-quartz solid solution, and generally tends to become cloudy when made into crystallized glass, but by suitably adjusting the glass composition and firing conditions, the refractive index difference between the crystal phase containing β-spodumene solid solution and the remaining glass phase can be reduced, and in this case, the crystallized glass is less likely to become cloudy. The Li2O-Al2O3-SiO2-based crystallized glass plate 2 may contain crystals such as β-spodumene solid solution as long as they do not adversely affect coloring, etc.
[0078] The Li2O-Al2O3-SiO2 crystallized glass plate 2 has a thermal expansion coefficient of 30×10 -7 / ℃ or less, 25×10 -7 / ℃ or less, 20×10 -7 / ℃ or less, 18×10 -7 / ℃ or less, 16×10 -7 / ℃ or less, 14×10 -7 / ℃ or less, 13×10 -7 / ℃ or less, 12×10 -7 / ℃ or less, 11×10 -7 / ℃ or less, 10×10 -7 / ℃ or less, 9×10 -7 / ℃ or less, 8×10 -7 / ℃ or less, 7×10 -7 / ℃ or less, 6×10 -7 / ℃ or less, 5×10 -7 / ℃ or less, 4×10 -7 / ℃ or less, 3×10 -7 / ℃ or less, especially 2×10 -7 / °C or less. When dimensional stability and / or thermal shock resistance are particularly required, it is preferable that the temperature is -5×10 -7 / ℃~5×10 -7 / ℃, -3×10 -7 / ℃~3×10 -7 / ℃, -2.5×10 -7 / ℃~2.5×10 -7 / ℃, -2×10 -7 / ℃~2×10 -7 / ℃, -1.5×10 -7 / ℃~1.5×10 -7 / ℃, -1×10 -7 / ℃~1×10 -7 / ℃, especially -0.5×10 -7 / ℃~0.5×10 -7 / °C.
[0079] The Li2O-Al2O3-SiO2 crystallized glass plate 2 has a thermal expansion coefficient of 30×10 -7 / ℃ or less, 25×10 -7 / ℃ or less, 20×10 -7 / ℃ or less, 18×10 -7 / ℃ or less, 16×10 -7 / ℃ or less, 14×10 -7 / ℃ or less, 13×10 -7 / ℃ or less, 12×10 -7 / ℃ or less, 11×10 -7 / ℃ or less, 10×10 -7 / ℃ or less, 9×10 -7 / ℃ or less, 8×10 -7 / ℃ or less, 7×10 -7 / ℃ or less, 6×10 -7 / ℃ or less, 5×10 -7 / ℃ or less, 4×10 -7 / ℃ or less, especially 3×10 -7 / °C or less. In addition, when dimensional stability and / or thermal shock resistance are particularly required, it is preferable that the temperature is -15×10 -7 / ℃~15×10 -7 / ℃, -12×10 -7 / ℃~12×10 -7 / ℃, -10×10 -7 / ℃~10×10 -7 / ℃, -8×10 -7 / ℃~8×10 -7 / ℃, -6×10 -7 / ℃~6×10 -7 / ℃, -5×10 -7 / ℃~5×10 -7 / ℃, -4.5×10 -7 / ℃~4.5×10 -7 / ℃, -4×10 -7 / ℃~4×10 -7 / ℃, -3.5×10 -7 / ℃~3.5×10 -7 / ℃, -3×10 -7 / ℃~3×10 -7 / ℃, -2.5×10 -7 / ℃~2.5×10 -7 / ℃, -2×10 -7 / ℃~2×10 -7 / ℃, -1.5×10 -7 / ℃~1.5×10 -7 / ℃, -1×10 -7 / ℃~1×10 -7 / ℃, especially -0.5×10 -7 / ℃~0.5×10 -7 / °C.
[0080] The Li2O-Al2O3-SiO2-based crystallized glass plate 2 preferably has a Young's modulus of 60 to 120 GPa, 70 to 110 GPa, 75 to 110 GPa, 75 to 105 GPa, or 80 to 105 GPa, particularly 80 to 100 GPa. If the Young's modulus is too low or too high, the mechanical strength of the glass article 1 is likely to decrease.
[0081] The Li2O-Al2O3-SiO2-based crystallized glass plate 2 preferably has a modulus of rigidity of 25 to 50 GPa, 27 to 48 GPa, or 29 to 46 GPa, particularly preferably 30 to 45 GPa. If the modulus of rigidity is too low or too high, the mechanical strength of the glass article 1 is likely to decrease.
[0082] The Li2O-Al2O3-SiO2-based crystallized glass plate 2 preferably has a Poisson's ratio of 0.35 or less, 0.32 or less, 0.3 or less, 0.28 or less, 0.26 or less, and particularly preferably 0.25 or less. If the Poisson's ratio is too large, the mechanical strength of the glass article 1 is likely to decrease.
[0083] The Li2O-Al2O3-SiO2-based crystallized glass plate 2 before crystallization has a density of 2.30 to 2.60 g / cm 3 , 2.32~2.58g / cm 3 , 2.34~2.56g / cm 3 , 2.36~2.54g / cm 3 , 2.38~2.52g / cm 3 , 2.39~2.51g / cm 3 , especially 2.40~2.50g / cm 3 If the density of the crystallizable glass is too low, the gas permeability before crystallization is deteriorated, and the glass may be contaminated during storage. On the other hand, if the density of the crystallizable glass is too high, the weight per unit area is large, and handling becomes difficult.
[0084] The Li2O-Al2O3-SiO2 crystallized glass plate 2 (after crystallization) has a density of 2.40 to 2.80 g / cm 3 , 2.42~2.78g / cm 3 , 2.44~2.76g / cm 3 , 2.46~2.74g / cm 3 , especially 2.47 to 2.73 g / cm 3 It is preferable that the density of the crystallized glass is too low, the gas permeability of the crystallized glass may deteriorate, and the colored layer may be contaminated. On the other hand, if the density of the crystallized glass is too high, the weight per unit area becomes large, making it difficult to handle. In addition, the density of the crystallized glass (after crystallization) is an index for determining whether the glass is sufficiently crystallized. Specifically, for the same glass, the higher the density (the greater the density difference between the original glass and the crystallized glass), the more the crystallization has progressed.
[0085] The density change rate of the Li2O-Al2O3-SiO2 crystallized glass plate 2 is {(density after crystallization (g / cm 3 )-Density before crystallization (g / cm 3 ) / density before crystallization (g / cm 3 )}×100(%), where the density before crystallization is the density after the glass after melting is held at 700°C for 30 minutes and cooled to room temperature at 3°C / min, and the density after crystallization is the density after crystallization treatment under a specified condition. The density change rate is preferably 0.01 to 10%, 0.05 to 8%, 0.1 to 8%, 0.3 to 8%, 0.5 to 8%, 0.9 to 8%, 1 to 7.8%, 1 to 7.4%, 1 to 7%, 1.2 to 7%, 1.6 to 7%, 2 to 7%, 2 to 6.8%, 2 to 6.5%, 2 to 6.3%, 2 to 6.2%, 2 to 6.1%, 2 to 6%, 2.5 to 5%, 2.6 to 4.5%, or 2.8 to 3.8%. If the density change rate before and after crystallization is reduced, the breakage rate after crystallization can be reduced, and scattering between the glass and the glass matrix can be reduced, making it possible to obtain crystallized glass with high transmittance. In particular, in the region where the TiO2 content is less than 2.0% (especially less than 0.5%), scattering can be significantly reduced in reducing coloring factors other than absorption by TiO2, etc., which contributes to improving transmittance.
[0086] The Li2O-Al2O3-SiO2 crystallized glass plate 2 may be chemically strengthened. The conditions of the chemical strengthening treatment may be appropriately selected, such as the treatment time and temperature, taking into consideration the glass composition, the degree of crystallization, and the type of molten salt. For example, a glass composition containing a large amount of Na2O that may be contained in the remaining glass may be selected, or the degree of crystallization may be intentionally reduced, so that chemical strengthening after crystallization is easier. The molten salt may contain an alkali metal such as Li, Na, or K alone or in combination. In addition to the usual one-stage strengthening, multi-stage chemical strengthening may be selected. In addition, the Li2O content of ... Furthermore, when the crystallinity of the sample surface is low, the glass phase increases on the surface, and the chemical resistance and gas barrier properties can be improved by selecting the glass composition.
[0087] Next, a method for producing the Li2O-Al2O3-SiO2 crystallized glass plate 2 will be described.
[0088] First, a raw material batch prepared to obtain glass of the above composition is put into a glass melting furnace, melted at 1500 to 1750°C, and then molded. The glass may be melted by a flame melting method using a burner or an electric melting method using electric heating. Melting by laser irradiation or plasma is also possible.
[0089] Next, the obtained crystallizable glass (crystallizable glass before crystallization) is heat-treated to crystallize. As for the crystallization conditions, first, nucleation is performed at 700 to 950°C (preferably 750 to 900°C) for 0.1 to 100 hours (preferably 1 to 60 hours), followed by crystal growth at 800 to 1050°C (preferably 800 to 1000°C) for 0.1 to 50 hours (preferably 0.2 to 10 hours). In this way, a transparent Li2O-Al2O3-SiO2-based crystallized glass (thickness: 1 to 10 mm) in which β-quartz solid solution crystals are precipitated as the main crystals can be obtained. Note that the heat treatment may be performed only at a certain temperature, or may be performed stepwise by holding at two or more levels of temperature, or may be heated while applying a temperature gradient.
[0090] Crystallization may also be promoted by applying or irradiating sound waves or electromagnetic waves. Furthermore, the cooling rate of the crystallized glass at a high temperature may be performed at a certain temperature gradient, or may be performed at two or more levels of temperature gradient. If sufficient thermal shock resistance is desired, it is desirable to control the cooling rate to sufficiently relax the structure of the remaining glass phase. The average cooling rate from 800°C to 25°C is preferably 3000°C / min, 1000°C / min or less, 500°C / min or less, 400°C / min or less, 300°C / min or less, 200°C / min or less, 100°C / min or less, 50°C / min or less, 25°C / min or less, 10°C / min or less, and particularly 5°C / min or less in the inner part of the thickness farthest from the surface of the crystallized glass. In addition, when dimensional stability over a long period of time is desired, the cooling rate is preferably 2.5°C / min or less, 1°C / min or less, 0.5°C / min or less, 0.1°C / min or less, 0.05°C / min or less, 0.01°C / min or less, 0.005°C / min or less, 0.001°C / min or less, 0.0005°C / min or less, and particularly 0.0001°C / min or less. Except for the case of physical strengthening treatment by air cooling, water cooling, etc., it is desirable that the cooling rate of the crystallized glass is close to the cooling rate of the glass surface and the cooling rate of the inner wall thickness farthest from the glass surface. The value obtained by dividing the cooling rate of the inner wall thickness farthest from the surface by the cooling rate of the surface is preferably 0.0001 to 1, 0.001 to 1, 0.01 to 1, 0.1 to 1, 0.5 to 1, 0.8 to 1, 0.9 to 1, and particularly 1. By being close to 1, residual strain is unlikely to occur at all positions of the crystallized glass sample, and long-term dimensional stability is easily obtained. The cooling rate of the surface can be estimated using a contact thermometer or a radiation thermometer, and the internal temperature can be estimated by placing the high-temperature crystallized glass in a cooling medium and measuring the heat quantity and rate of heat change of the cooling medium, and then using this numerical data and the specific heat and thermal conductivity of the crystallized glass and the cooling medium.
[0091] (Colored layer 3) The colored layer 3 preferably contains a silicone resin, a colored pigment, and an extender pigment. From the viewpoints of dispersibility and heat resistance, the content ratio of the colored pigment to the extender pigment in the colored layer 3 (colored pigment / extender pigment) is preferably 1 to 6, particularly preferably 1.5 to 5.
[0092] The silicone resin contained in the colored layer 3 preferably has high heat resistance. For example, the silicone resin contained in the colored layer 3 is preferably a silicone resin in which the functional group directly bonded to the silicon atom is at least one of a methyl group and a phenyl group. In this case, discoloration of the colored layer 3 when the glass article 1 is heated to a high temperature can be easily suppressed.
[0093] The content of the silicone resin in the colored layer 3 is preferably 20 to 70 mass %, particularly 30 to 60 mass %. If the content of the silicone resin is too low, the heat resistance and impact resistance of the glass article 1 are likely to decrease. On the other hand, if the content of the silicone resin is too high, the mechanical strength of the glass article 1 is likely to decrease. The content of the silicone resin is the content when the entire material constituting the colored layer 3 is taken as 100 mass %.
[0094] The color pigment contained in the colored layer 3 is not particularly limited as long as it is a colored inorganic substance. Examples of the color pigment include white pigment powder such as TiO2 powder, ZrO2 powder, or ZrSiO4 powder, blue inorganic pigment powder containing Co, green inorganic pigment powder containing Co, Ti-Sb-Cr-based or Ti-Ni-based yellow inorganic pigment powder, Co-Si-based red inorganic pigment powder, brown inorganic pigment powder containing Fe, and black inorganic pigment powder containing Cu.
[0095] Specific examples of blue inorganic pigment powders containing Co include Co-Al or Co-Al-Ti inorganic pigment powders. Specific examples of Co-Al inorganic pigment powders include CoAl2O4 powder. Specific examples of Co-Al-Ti inorganic pigment powders include CoAl2O4-TiO2-Li2O powder.
[0096] Specific examples of green inorganic pigment powders containing Co include Co-Al-Cr or Co-Ni-Ti-Zn inorganic pigment powders. Specific examples of Co-Al-Cr inorganic pigment powders include Co(Al,Cr)2O4 powder. Specific examples of Co-Ni-Ti-Zn inorganic pigment powders include (Co,Ni,Zn)2TiO4 powder.
[0097] A specific example of the brown inorganic pigment powder containing Fe is, for example, an Fe-Zn-based inorganic pigment powder. A specific example of the Fe-Zn-based inorganic pigment powder is, for example, a (Zn,Fe)Fe2O4 powder.
[0098] Specific examples of black inorganic pigment powders containing Cu include Cu-Cr-based inorganic pigment powders and Cu-Fe-based inorganic pigment powders. Specific examples of Cu-Cr-based inorganic pigment powders include Cu(Cr,Mn)2O4 powder and Cu-Cr-Mn powder. Specific examples of Cu-Fe-based inorganic pigment powders include Cu-Fe-Mn powder.
[0099] These color pigments may be used alone or in combination of two or more kinds.
[0100] The content of the color pigment in the colored layer 3 is preferably 10 to 60 mass%, particularly 15 to 50 mass%. If the content of the color pigment is too low, the light blocking property and design property of the glass article 1 are likely to decrease. On the other hand, if the content of the color pigment is too high, the heat resistance and impact resistance of the glass article 1 are likely to decrease. The content of the color pigment is the content when the entire material constituting the colored layer 3 is taken as 100 mass%.
[0101] The average particle size of the color pigment is preferably 0.05 to 0.4 μm or more, particularly 0.1 to 0.3 μm. If the average particle size of the color pigment is too small, the paste in the manufacturing method described below tends to become highly viscous, and the printability tends to deteriorate. On the other hand, if the average particle size of the color pigment is too large, the heat resistance and impact resistance tend to deteriorate. The average particle size refers to the average particle size calculated from the volume-based distribution by the laser diffraction method.
[0102] The extender pigment contained in the colored layer 3 is an inorganic pigment powder different from the color pigment. The extender pigment is not particularly limited, but for example, talc, mica, etc. can be used.
[0103] These extender pigments may be used alone or in combination of two or more kinds.
[0104] The content of the body pigment in the colored layer 3 is preferably 5 to 60% by mass, and particularly preferably 10 to 40% by mass. If the content of the body pigment is too low, the mechanical strength of the glass article 1 is likely to decrease. On the other hand, if the content of the body pigment is too high, the heat resistance and impact resistance of the glass article 1 are likely to decrease. The content of the body pigment is the content when the entire material constituting the colored layer 3 is taken as 100% by mass.
[0105] The average particle size of the extender pigment is preferably 5 to 50 μm, particularly 10 to 45 μm. If the average particle size of the extender pigment is too small, the paste in the production method described below tends to have high viscosity, and printability tends to deteriorate. On the other hand, if the average particle size of the extender pigment is too large, heat resistance and impact resistance tend to deteriorate.
[0106] The total content of the coloring pigment and the extender pigment in the colored layer 3 is preferably 15 to 70% by mass, and particularly preferably 25 to 60% by mass. If the total content of the coloring pigment and the extender pigment is too low, the design and mechanical strength of the glass article 1 are likely to decrease. On the other hand, if the total content of the coloring pigment and the extender pigment is too high, the heat resistance and impact resistance of the glass article 1 are likely to decrease. The total content of the coloring pigment and the extender pigment is the total content when the entire material constituting the colored layer 3 is taken as 100% by mass.
[0107] There is no particular limitation on the thickness of the colored layer 3. The thickness of the colored layer 3 can be appropriately set depending on the light transmittance of the colored layer 3. The thickness of the colored layer 3 can be, for example, 1 to 15 μm.
[0108] (Method of Manufacturing Glass Article 1) The glass article 1 can be manufactured, for example, by the following manufacturing method.
[0109] First, a paste containing a silicone resin, a color pigment powder, and an extender pigment powder is prepared. At this time, the paste is prepared so that the content ratio of the color pigment powder to the extender pigment powder in the paste (color pigment / extender pigment) is more than 1 to 6. Next, the prepared paste is directly applied onto the back surface 2b of the Li2O-Al2O3-SiO2-based crystallized glass plate 2 and dried. In this way, the glass article 1 can be manufactured. Depending on the composition of the color layer 3, the glass article 1 may be obtained by firing after drying.
[0110] The glass article 1 may have an image display area, a video display area, a stereoscopic image display area, a stereoscopic video display area, a radio wave receiving area, a radio wave transmitting area, and a sound wave generating area.
[0111] The glass article 1 as described above is suitable for use as a top plate. EXAMPLES
[0112] The present invention will be described below based on examples, but the present invention is not limited to the following examples. Tables 1 to 30 show examples of the present invention (samples No. 1 to 98) and a comparative example (sample No. 99).
[0113] [Table 1]
[0114] [Table 2]
[0115] [Table 3]
[0116] [Table 4]
[0117] [Table 5]
[0118] [Table 6]
[0119] [Table 7]
[0120] [Table 8]
[0121] [Table 9]
[0122]
Table 10
[0123]
Table 11
[0124]
Table 12
[0125]
Table 13
[0126]
Table 14
[0127]
Table 15
[0128]
Table 16
[0129]
Table 17
[0130]
Table 18
[0131]
Table 19
[0132]
Table 20
[0133]
Table 21
[0134]
Table 22
[0135]
Table 23
[0136]
Table 24
[0137]
Table 25
[0138]
Table 26
[0139]
Table 27
[0140]
Table 28
[0141]
Table 29
[0142]
Table 30
[0143] (Preparation and evaluation of Li2O-Al2O3-SiO2 crystallized glass plates) First, each raw material was mixed in the form of oxide, hydroxide, carbonate, nitrate, etc. to obtain a glass having the composition shown in each table, and a glass batch was obtained (the composition shown in each table is the analytical value of the glass actually produced). The obtained glass batch was placed in a crucible containing platinum and rhodium, a reinforced platinum crucible not containing rhodium, a refractory crucible, or a quartz crucible, and melted at 1600°C for 4 to 100 hours, then heated to 1650 to 1680°C and melted for 0.5 to 20 hours, rolled to a thickness of 5 mm, and further heat-treated at 700°C for 30 minutes in an annealing furnace, and the annealing furnace was cooled to room temperature at 100°C / h to obtain a crystallizable glass. The melting was performed by an electric melting method that is widely used in the development of glass materials.
[0144] The Pt and Rh contents of the samples were analyzed using an ICP-MS device (Agilent8800, manufactured by AGILEINT TECHNOLOGY). First, the prepared glass samples were crushed and wetted with pure water, and then perchloric acid, nitric acid, sulfuric acid, hydrofluoric acid, etc. were added to melt them. The Pt and Rh contents of the samples were then measured using an ICP-MS. The Pt and Rh contents of each measurement sample were determined based on a calibration curve prepared using a previously prepared Pt and Rh solution with known concentrations. The measurement modes were Pt:He gas / HMI (low mode) and Rh:HEHe gas / HMI (medium mode), and the mass numbers were Pt:198 and Rh:103. The Li2O content of the prepared samples was analyzed using an atomic absorption spectrometer (ContrAA600, manufactured by Analytik Jena). The flow of melting the glass samples and the use of the calibration curves were basically the same as for the Pt and Rh analysis. As for other components, they were measured by ICP-MS or atomic absorption spectrometry in the same way as Pt, Rh, and Li2O, or glass samples with known concentrations previously examined using an ICP-MS or atomic absorption spectrometry were used as calibration curve samples, and calibration curves were then created using an XRF analyzer (RIGAKU ZSX PrimusIV) and the actual content of each component was determined from the XRF analysis values of the measurement sample based on the calibration curve. During XRF analysis, the tube voltage, tube current, exposure time, etc. were adjusted as necessary depending on the components being analyzed.
[0145] The crystallized glasses shown in each table were heat-treated at 750-900°C for 0.75-60 hours to form nuclei, and then further heat-treated at 800-1000°C for 0.25-3 hours to crystallize. Then, the glasses were heat-treated at 700°C for 30 minutes, and cooled to room temperature at 100°C / h. The obtained crystallized glasses were evaluated for transmittance, diffuse transmittance, brightness, chromaticity, precipitated crystals, average crystallite size, thermal expansion coefficient, density, Young's modulus, rigidity modulus, Poisson's ratio, and appearance. The transmittance, brightness, chromaticity, etc. of the crystallized glasses before crystallization were measured in the same manner as the crystallized glasses. The β-OH value, viscosity, and liquidus temperature of the crystallized glasses were also measured.
[0146] The transmittance, lightness, and chromaticity were evaluated by measuring a crystallized glass plate with a thickness of 3 mm, both sides of which were optically polished, using a spectrophotometer. A spectrophotometer V-670 manufactured by JASCO was used for the measurement. The V-670 was equipped with an integrating sphere unit "ISN-723", and the measured transmittance corresponds to the total light transmittance. The measurement wavelength range was 200 to 1500 nm, the scan speed was 200 nm / min, the sampling pitch was 1 nm, and the bandwidth was 5 nm in the wavelength range of 200 to 800 nm, and 20 nm in other wavelength ranges. Before the measurement, baseline correction (100% adjustment) and dark measurement (0% adjustment) were performed. The dark measurement was performed with the barium sulfate plate attached to the ISN-723 removed. Using the measured transmittance, tristimulus values XYZ were calculated based on JISZ8781-42013 and corresponding international standards, and lightness and chromaticity were calculated from each stimulus value (illuminant C / 10°). The diffuse transmittance of the crystallized glass was measured using the same model as above, with the barium sulfate plate attached to the ISN-723 removed and the measurement sample placed thereon.
[0147] The precipitated crystals were evaluated using an X-ray diffractometer (Rigaku Smart Lab, fully automatic multipurpose horizontal X-ray diffractometer). The scan mode was 2θ / θ measurement, the scan type was continuous scan, the scattering and divergence slit width was 1°, the receiving slit width was 0.2°, the measurement range was 10-60°, the measurement step was 0.1°, and the scan speed was 5° / min. The main crystals and crystal grain size were evaluated using the analysis software installed in the package of the same model. As the precipitated crystal species identified as the main crystals, β-quartz solid solution is shown in the table as "β-Q". The average crystallite size of the main crystals was calculated using the measured X-ray diffraction peaks based on the Debeye-Scherrer method. In the measurement for calculating the average crystallite size, the scan speed was 1° / min.
[0148] The thermal expansion coefficient was evaluated by the average linear thermal expansion coefficient measured in the temperature ranges of 30 to 380°C and 30 to 750°C using a crystallized glass sample processed to 20mm x 3.8mmφ. A NETZSCH dilatometer was used for the measurement. In addition, the same measuring device was used to measure the thermal expansion curve in the temperature range of 30 to 750°C, and the glass transition point of the crystallized glass before crystallization was evaluated by calculating the inflection point.
[0149] The Young's modulus, rigidity modulus, and Poisson's ratio were measured at room temperature using a free resonance type elastic modulus measuring device (JE-RT3, manufactured by Nippon Technoplus) for plate samples (40 mm x 20 mm x 20 mm) whose surfaces had been polished with a polishing solution containing dispersed No. 1200 alumina powder.
[0150] The density was evaluated by the Archimedes method.
[0151] The strain point and annealing point were evaluated by the fiber elongation method. The crystallizable glass was prepared into fiber samples by hand drawing.
[0152] The β-OH value was calculated by measuring the transmittance of the glass using FT-IR Frontier (manufactured by Perkin Elmer) and using the following formula. The scan speed was 100 μm / min and the sampling pitch was 1 cm.-1 The number of scans was 10 per measurement.
[0153] β-OH value = (1 / X)log10(T1 / T2) X: Glass thickness (mm) T1: Reference wavelength 3846cm -1 Transmittance (%) T2: Hydroxyl group absorption wavelength 3600cm -1 Minimum transmittance (%) near
[0154] The high-temperature viscosity was evaluated by the platinum ball pulling method. For the evaluation, the lump glass sample was crushed to the appropriate size and placed in an alumina crucible while minimizing the inclusion of air bubbles. The alumina crucible was then heated to turn the sample into a molten liquid, and the viscosity of the glass was measured at multiple temperatures. The constants of the Vogel-Fulcher equation were calculated to create a viscosity curve, and the temperature at each viscosity was calculated.
[0155] The liquidus temperature was evaluated by the following method. First, a platinum boat of about 120 x 20 x 10 mm was filled with glass powder aligned to 300 to 500 micrometers, which was then placed in an electric furnace and melted at 1600 ° C for 30 minutes. After that, it was transferred to an electric furnace with a linear temperature gradient and placed in it for 20 hours to precipitate devitrification. After the measurement sample was air-cooled to room temperature, the devitrification precipitated at the interface between the platinum boat and the glass was observed, and the temperature at the devitrification point was calculated from the temperature gradient graph of the electric furnace to determine the liquidus temperature. In addition, the obtained liquidus temperature was inserted into the high-temperature viscosity curve of the glass, and the viscosity corresponding to the liquidus temperature was determined as the liquidus viscosity. It was found that the initial phase of the glass listed in each table was mainly ZrO2 based on the results of X-ray diffraction, composition analysis, etc. (Hitachi scanning electron microscope Hitachi S3400N TyPE2, Horiba EMAX ENERGY EX250X).
[0156] The appearance was evaluated by visually checking the color tone of the crystallized glass. Visual inspection was performed against a white background and a black background, under indoor lighting and sunlight (8:00, 12:00, and 16:00 on sunny and cloudy days in January, April, July, and October). The color tone was judged comprehensively from the results of each visual inspection.
[0157] (Production and Evaluation of Glass Articles) First, 29.9 parts by mass of silicone resin (resin solid content), 35.2 parts by mass of white TiO2 powder pigment (average particle size: 0.2 μm), and 11.7 parts by mass of talc (average particle size: 20 μm) as an extender pigment were mixed, and 23.2 parts by mass of organic solvent were added to prepare a paste. Next, this paste was screen-printed on the entire Li2O-Al2O3-SiO2 crystallized glass plate prepared as above to a thickness of 10 μm. Then, it was dried at 70 ° C for 10 minutes, and further baked at 320 ° C for 15 minutes to form a white colored layer, and a glass article was obtained.
[0158] When the color of the obtained glass article was checked, it was found that Samples No. 1 to 98, which are examples, were white in color similar to the colored layer, whereas Sample No. 99, which is a comparative example, was yellowish compared to the colored layer, impairing the color of the colored layer.
[0159] FIG. 2 shows the measurement results of the reflection chromaticity of sample No. 89 (3 mm thick) and a glass article in which a white colored layer is formed on an existing Li2O-Al2O3-SiO2-based crystallized glass plate (3 mm thick, chromaticity b* measured by the above-mentioned method is more than 5) that is distributed on the top plate market (reflection chromaticity was measured using CM-600d manufactured by Konica Minolta). As is clear from FIG. 2, sample No. 89 had no difference in reflection chromaticity with the colored layer, and was able to express the color of the colored layer. On the other hand, the existing Li2O-Al2O3-SiO2-based crystallized glass plate had a large difference in reflection chromaticity with the colored layer, and was unable to express the color of the colored layer. The effect of the present invention has also been confirmed for colored layers of red, pink, blue, silver, green, etc. [Explanation of symbols]
[0160] 1. Glass items 2...Li2O-Al2O3-SiO2 crystallized glass plate 2a…Cooking surface 2b…Back side 3…Colored layer
Claims
1. Lithium Ion (L*) has a lightness L* of 70 or more, a chromaticity a* of ±5 or less, and a chromaticity b* of ±5 or less at a thickness of 3 mm. 2 O-Al 2 O 3 -SiO 2 Crystallized glass plate and Li 2 O-Al 2 O 3 -SiO 2 A colored layer is formed on the back surface of the crystallized glass plate, The glass article is characterized in that the Li 2 O—Al 2 O 3 —SiO 2 system crystallized glass plate contains, in mass %, 0.02 to 10% of P 2 O 5 and 2.15 to 20% of ZrO 2 .
2. Li 2 O-Al 2 O 3 -SiO 2 The crystallized glass plate is composed of, in mass%, SiO 2 40-90%, Al 2 O 3 5-30%, Li 2 O 1-10%, TiO 2 0-2% or less, SnO 2 0-20%, ZrO 2 2.15-20%, MgO 0-10%, P 2 O 5 0.02-10%, Sb 2 O 3 +As 2 O 3 2. The glass article according to claim 1, characterized in that it contains 0 to less than 2%.
3. Li 2 O-Al 2 O 3 -SiO 2 3. The glass article according to claim 1, wherein the crystallized glass plate has a colorless and transparent appearance.
4. Li 2 O-Al 2 O 3 -SiO 2 4. The glass article according to claim 1, wherein the crystallized glass plate has a thickness of 3 mm and a transmittance of 10% or more at a wavelength of 300 nm.
5. Li 2 O-Al 2 O 3 -SiO 2 The thermal expansion coefficient of the crystallized glass plate at 30 to 380°C is 30 x 10 -7 5. The glass article according to claim 1, wherein the glass has a melting point of 100° C. or less.
6. Li 2 O-Al 2 O 3 -SiO 2 The thermal expansion coefficient of the crystallized glass plate at 30 to 750°C is 30 x 10 -7 6. The glass article according to claim 1, wherein the glass has a melting point of 100° C. or less.
7. A top plate for a cooker, comprising the glass article according to any one of claims 1 to 6.
Citation Information
Patent Citations
JP1964-021049B
JP1965020182Y1
Li2o-al2o3-sio2-based transparent crystallized glass for combustion apparatus window
JP1989308845A
Transparent, colorless, titania-free, beta-quartz-glass-ceramic material
JP2010510952A
Crystallizable lithium aluminum silicate glass, and transparent glass ceramic produced therefrom, and method for producing glass and glass ceramic, and use of glass ceramic
JP2017222561A